Effect Of Listing Age, Company Performance, And Shareholder Pressure On Integrated Reporting - Imam, Gahenza Raihan Talian; Lestari, Tri Utami (UNIVERSITAS PAKUAN, 2019)
Integrated Reporting is a report that contains financial and non-financial information of the organization with the aim of being a brief communication tool of organizational performance in the context of the external environment and leads to the creation, preservation of value (value) both short, medium, and long term. This study aims to examine whether listing age, company performance, and shareholder pressure can affect companies in reporting information according to Integrated Reporting content. Research is modified because it uses existing theories by including new variables as research variables. This research uses company data from the basic material sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. Purposive sampling technique resulted in a total of 63 companies in the raw goods sector (basic material) being used as the object of this study. The results in this study show that listing age, company performance, and shareholder pressure simultaneously have a significant effect on Integrated Reporting. Partially, listing age and shareholder pressure have a positive effect on Integrated Reporting. While the company's performance does not affect Integrated Reporting.